Educational Transmission Across Three Generations and the Number of Grandparents’ Children Mediation in China - Weijuan Wu; Xuelin Yang; Yehui Lao (SAGE Open)
This article uses survey data from the China Health and Retirement Longitudinal Survey (CHARLS2015) to test whether the educational level across three generations are transmitted within families and whether number of grandparents’ children influences these intergenerational transmissions in China. We obtain evidences that the educational level across three generations is transmitted within families, grandparents’ education has a direct and indirect effect on grandchildren’s education. After rigorous robustness tests, the results remain still valid. Educational intergenerational transmission from grandparents to grandchildren is partly explained by parental education. By gender heterogeneity analysis, we find there are son preferences on education three-generational transmission in China. Our results also show that number of grandparents’ children reduces educational association between grandparents and grandchildren. These findings show that different family structures have led to different educational transmission trajectories for families across multi-generation, which is an important factor giving rise to education inequality. This finding not only provides a new explanation for the complexity of family educational transmission mechanisms but also offers an important variable consideration for understanding the roots and persistence of educational inequality. Understanding how the number of grandparents’ children affects educational transmission provides insight into the mechanisms behind the formation of educational inequality and offers theoretical support for improving the equitable distribution of educational resources.